2012 IEEE International Conference on Development and Learning and Epigenetic Robotics (ICDL) 2012
DOI: 10.1109/devlrn.2012.6400879
|View full text |Cite
|
Sign up to set email alerts
|

Co-development of information transfer within and between infant and caregiver

Abstract: This paper presents a computational approach to measuring information transfer in infant-caregiver interaction. It is supposed that both an infant and a caregiver mutually shape the interaction by sending various signals to each other, of which the dynamic structure changes according to the infant's age. We investigated such developmental change both in infants and caregivers by measuring transfer entropy within and between their body movements. Our analysis demonstrated that infants significantly improve thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…There are also some studies on infants' behavior analysis [16][5] [15]. In these studies, the motion of infants and adults (parents or caregiver) are usually tracked and detected by sensors.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…There are also some studies on infants' behavior analysis [16][5] [15]. In these studies, the motion of infants and adults (parents or caregiver) are usually tracked and detected by sensors.…”
Section: Related Workmentioning
confidence: 99%
“…In these studies, the motion of infants and adults (parents or caregiver) are usually tracked and detected by sensors. The information flow within and between their body movements are measured by transfer entropy [5] [15], based on which the interaction exchange and interaction between infants and parents can be computed.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Fukuyama et al [9] demonstrated the reverse effect in which caregivers' motionese is dynamically affected by infants' actions. Nagai et al [10] revealed the co-development of caregivers and infants by measuring information transfer in their dynamic interactions. In the context of others' action observation, infants can predict the goals of perceived actions [11].…”
Section: Introductionmentioning
confidence: 99%
“…The latter two values represent body coordination Analysis of the dynamical structure of infant-caregiver interaction (Adapted fromNagai et al 2012). Higher values of T M j !m i and/or T m i !M j indicate more contingency between the infant and the caregiver.…”
mentioning
confidence: 99%